مبدأ شخصية العقوبة والمساواة فيها في الشريعة الإسلامية القانون الجنائي الإيراني أنموذجًا - Arif, A.; Salami, F. (Universiti Sains Islam Malaysia, 2024)
The aim of this study isto review two principles of "individualization of punishments" and "equality of punishments" in Islam, and the topic wasinvestigated in the Islamic punishment law in Iran. The inductive method isused to study and induce the jurisconsults sayings and articles of law in the compiled writings on the related topic, and the two mentioned principles were analyzed using the analytical and comparative methods. Based on the mentioned methods and referring to the definition and concept of punishment in Islam and Iranian criminal law, the author concluded that punishments have common principles and properties which are dominant in all punishments and manifested in the principles of the legality of punishments, equality of punishments and individualization of punishments. Moreover, the author studied the relationship between the principle of individualization of punishment and paying blood money by the Aqilah (blood relative/solidarity group) in unintentional crimes (error) and concluded that the Aqilah system is completely based on general and proved rules in Islam, and it is not excepted from the principle of individualization of punishment.